But what about that nice house you own? The impact of asset tests in minimum income schemes in Europe: An empirical exploration. (February 2021) - Marchal, Sarah; Kuypers, Sarah; Marx, Ive; Verbist, Gerlinde
Means-tested transfer schemes in Europe and elsewhere tend to include not only income tests but also asset tests of various sorts. The role of asset tests in minimum income protection provisions has been extensively researched in the Anglo-Saxon context. Far fewer authors have assessed the role of asset tests on social policy in a continental European context. Although asset tests may be useful in singling out the more deserving of the poor, we know relatively little of their actual impact on eligibility and social outcomes in European welfare states. This paper looks at the prevalence and design of asset tests in European minimum income protection schemes. We distinguish between two main types of asset tests: outright disqualification when assets reach a certain value, versus a more gradual tapering at a fictional rate of return. We then analyse in greater detail how asset tests in Belgium and Germany, as representatives of these two types, affect minimum income protection eligibility and poverty outcomes. We use the EUROMOD microsimulation model on the Household Finance and Consumption Survey data in order to assess the effects of asset tests. This survey was explicitly designed to more realistically reflect assets and capital incomes.